A Molecular Dynamics Analysis on Interfacial Thermal Resistance between Particle and Medium in Light-Induced Heat Transfer of Plasmonic Nanofluid - Zhao, Chang (Langmuir : the ACS journal of surfaces and colloids, 2022)
Light-induced heat transfer process of plasmonic nanofluids is critical for many applications, but the energy conversion pathway still remains controversial. In this work, we develop a calculation model based on the combination of the electromagnetic theory and molecular dynamics (MD) simulation to investigate the impact of the localized surface plasmon resonance (LSPR) on the heat transfer between nanoparticles and the surrounding medium in gold and silver nanofluids. It is found that the LSPR-induced enhanced electric field (EEF) can obviously reduce the interfacial thermal resistance to promote the heat transfer process, especially in silver nanofluids. The results reveal that the movement of water molecules can be violently perturbed by the EEF to overcome the binding force of nanoparticles, and therefore the energy transfer process in water molecules can be obviously enhanced. The effect of EEF is significant, especially in the initial heating stages when the temperature of the nanoparticles is relatively low. When the silver nanoparticle temperature is 400 K, the relative reduction ratio of the interfacial thermal resistance can reach 19.0% under the effect of the LSPR-induced EEF. The results also indicate that two different energy conversion mechanisms: photothermal and photoexcited electric-field enhancement are likely to coexist and jointly impact the heat transfer process in plasmonic nanofluids, and the effect of the latter cannot be neglected. This work provides some new insights for a deeper understanding of the light-induced heat transfer process in plasmonic nanofluids